Pengaruh Pendidikan Kesehatan Terhadap Pelaksanaan Rentang Gerak Sendi Aktif Post Operasi Pada Pasien Fraktur Ekstremitas di Ruang Bedah Trauma Center RSUP DR. M. Djamil Padang : The Effect of Health Education on the Implementation of Postoperative Active Joint Range of Motion in Limb Fracture Patients in the Trauma Center Operating Room of DR. M. Djamil Padang Hospital - Vivi Oktasari; Atih Rahayuningsih; Mira Susanti (NERS Jurnal Keperawatan, 2013)
Mobilization is an important activity in the postoperative recovery to prevent complications, one of which contractures. Mobilization especially Range of Motion exercises can improve blood circulation which will speed healing and reduce pain. Immobilization in a long time because fracture will stimulate muscle artrofi skletal especially extremity which causes decreased muscle strength up to 5.5% per day. To increase knowledge the fracture patients about exercises must be do post operative is through health education preoperative. The goal of this research was to know effect of health education to knowledge and implementation ROM active post ORIF in patients with fractures of the extremity. Design of reseach is quasy experiment with Post-test Only Control Group Design. Taking of sampling using accidental sampling technique, 20 patients with fractures of extremity plan ORIF surgery divided 2 groups: 10 patients to be experiment group and 10 patients to be control group. Analyzing the data is using independent t-test. The result showed that there were significant differences in knowledge scores (p = 0.000), scores of implementation (p = 0.000) among patients who received health education and patient are not given health education. it is suggested that nurses as service providers can implement health education preoperative especially range of motion exercises on the extremity fracture patients as a nursing intervention in a hospital to improve patients knowledge about postoperative exercises and motivate the patient to do range of motion exercises postoperative.